Pelaksanaan Fungsi Pengawasan DPRD Terhadap Peraturan Daerah - Chabib Faturrohman, Muhamad; Sudarmanto, Kukuh; Junaidi, Muhammad; Sukimin, Sukimin (Universitas Semarang, 2023)
The purpose of this writing is to review and know the supervisory function of the DPRD, to determine the answer and problem solving to obstacles or obstacles in the supervision of the DPRD, in the implementation of regional regulations and mayoral regulations in the city of Semarang. Functions, duties, authority of the DPRD of Semarang city play less optimally or less maximally carry out the function of supervision on the implementation of local regulations and mayoral regulations. So that the supervisory function carried out by the DPRD has not been or is not felt by the community which raises the assumption that dprd supervision is less effective and not in accordance with the expectations of the community. The results showed that there is still weak supervision by the DPRD, against local regulations or mayoral regulations, indicated there are still local regulations or regulations that conflict with the regulations above, Then the constraints in the supervisory function of the number of members of the Semarang city DPRD have not understood the supervisory function of the implementation of regional regulations and mayoral regulations due to their educational background and still attach importance to political groups or parties. Maximize or improve in carrying out the supervisory function of the Semarang city DPRD against local regulations and mayoral regulations, in accordance with Law number 23 of 2014 concerning local government. Tujuan penulisan ini untuk mengkaji dan mengetahui fungsi pengawasan DPRD, untuk menentukan jawaban dan pemecahan masalah terhadap kendala atau hambatan dalam pengawasan DPRD, dalam pelaksanaan Peraturan Daerah dan Peraturan Walikota di Kota Semarang.Fungsi, tugas, wewenang DPRD kota Semarang kurang berperan secara optimal atau kurang maksimal mengemban fungsi pengawasan terhadap pelaksanaan peraturan daerah dan peraturan walikota. Sehingga fungsi pengawasan yang dijalankan DPRD belum atau tidak dirasakan oleh masyarakat yang menimbulkan anggapan bahwa pengawasan DPRD kurang efektif dan tidak sesuai dengan harapan masyarakat. Hasil penelitian menunjukkan bahwa masih Lemahnya pengawasan oleh DPRD, terhadap peraturan daerah atau peraturan walikota, diindikasi masih ada peraturan daerah atau perwal yang bertentangan dengan peraturan diatasnya, Kemudian kendala dalam fungsi pengawasan banyaknya Anggota DPRD kota Semarang belum memahami fungsi pengawasan terhadap pelaksanaan Peraturan Daerah dan Peraturan Walikota dikarenakan oleh latar belakang Pendidikan dan masih mementingkang kelompok atau partai politik. Maksimalkan atau tingkatkan dalam menjalankan fungsi pengawasan DPRD kota Semarang terhadap peraturan daerah dan peraturan walikota, sesuai dengan Undang-undang nomor 23 Tahun 2014 tentang pemerintah daerah.